Technical demands of the various playing positions in the qualifying matches for the European football championship - Kubayi, A. (International Journal of Performance Analysis in Sport, 2021)
This study investigated the technical demands on football players, based on their various playing positions, during the qualifying matches for the European Football Championship. Data were obtained from the InStat database. The sample consisted of 314 players grouped into the following five playing positions: central defenders (n = 89), wide defenders (n = 58), central midfielders (n = 85), wide midfielders (n = 51), and forwards (n = 31). The results showed that forwards had a significantly (p < 0.01) greater number of shots than players in other positions. Central midfielders performed a significantly (p < 0.01) greater number of passes than players in other positions, with a large effect when compared to forwards (ES: 1.38). Furthermore, wide midfielders made the highest number of crosses compared to players in other positions, but they showed a trivial difference when compared to wide defenders (ES: 0.10). Forwards` tendency to lose the ball was significantly (p < 0.01) higher than that for other positions, with a very large effect when compared to central defenders (ES: 2.41). These results may assist football coaches in preparing players to meet the game`s technical requirements, thus increasing the likelihood of qualifying for the European Football Championship.